2019
DOI: 10.2147/cmar.s207084
|View full text |Cite
|
Sign up to set email alerts
|

<p>Long noncoding RNA Linc00460 promotes breast cancer progression by regulating the miR-489-5p/FGF7/AKT axis</p>

Abstract: Purpose: Evidence indicates that long noncoding RNAs (lncRNA) possess important roles in various cellular processes and that dysregulation of lncRNAs promotes tumor progression. However, the expression patterns and biological functions of many specific lncRNAs in breast cancer remain to be determined. Methods: Quantitative real-time polymerase chain reaction was performed to detect Linc00460, miR-489-5p and FGF7 expression. Protein levels were determined using Western blot. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 43 publications
1
60
0
Order By: Relevance
“…FGF7 belongs to fibroblast growth factor (FGF) family and possess mitogenic and cell survival activities. Zhu et al reported that FGF7 could promote breast cancer progression through AKT signaling pathway [ 39 ]. In GC, several studies indicated that FGF7 might play a role in GC cell proliferation and metastasis [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…FGF7 belongs to fibroblast growth factor (FGF) family and possess mitogenic and cell survival activities. Zhu et al reported that FGF7 could promote breast cancer progression through AKT signaling pathway [ 39 ]. In GC, several studies indicated that FGF7 might play a role in GC cell proliferation and metastasis [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In glioma, LINC00460 has been demonstrated to be overexpressed in cancer tissues and cell lines, and to promote cancer cell progression by negatively regulating miR-320a (23). Additionally, a recent study reported that LINC00460 could promote breast cancer cell migration, invasion and proliferation by targeting the miR-489-5p/fibroblast growth factor 7/AKT axis (24). Notably, nicotine has been found to facilitate carcinogenesis in the bronchus by activating LINC00460 and the PI3K/AKT signaling pathway (25).…”
Section: Discussionmentioning
confidence: 99%
“…Via targeting of the miR-302c-5p/FOXA1 axis, LINC00460 can facilitate tumor growth in LUAD [31]. Similarly, LINC00460 has also been confirmed to promote the progression of multiple cancers through different target genes [32][33][34]. The last lncRNA, DGCR5, is slightly different because when it is highly expressed it exerts anticancer activity in various cancers, including gastric cancer, hepatocellular carcinoma, cervical cancer, and bladder cancer, suggesting a good prognosis [35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%